Low temperature reduces the energetic requirement for the CO2 concentrating mechanism in diatoms. Issue 1 (13th October 2014) - Kranz, Sven A.; Young, Jodi N.; Hopkinson, Brian M.; Goldman, Johanna A. L.; Tortell, Philippe D.; Morel, François M. M.
Summary The goal of this study is to investigate the CO2 concentrating mechanism (CCM) of the dominant phytoplankton species during the growing season at Palmer station in the Western Antarctic Peninsula. Key CCM parameters (cellular half‐saturation constants for CO2 fixation, carbonic anhydrase activity, CO2/HCO3− uptake, δ13Corg) in natural phytoplankton assemblages were determined. Those results, together with additional measurements on CO2 membrane permeability from Fragilariopsis cylindrus laboratory cultures, were used to develop a numerical model of the CCM of cold water diatoms. The field data demonstrate that the dominant species throughout the season possess an effective CCM, which achieves near saturation of CO2 for fixation. The model provides a means to examine the role of eCA activity and HCO3−/CO2 uptake in the functioning of the CCM. According to the model, the increase in δ13Corg during the bloom results chiefly from decreasing ambient CO2 concentration (which reduces the gross diffusive flux across the membrane) rather than a shift in inorganic carbon uptake from CO2 to HCO3−. The CCM of diatoms in the Western Antarctic Peninsula functions with a relatively small expenditure of energy, resulting chiefly from the low half‐saturation constant for Rubisco at cold temperatures.